A Statewide Parenting Alternative Sentencing Program: Description and Preliminary Outcomes. (2nd January 2017) - Aguiar, Chyla M.; Leavell, Susan
ABSTRACT: The Washington State Legislature created the Parenting Sentencing Alternative in 2010, authorizing a substitute to total confinement for parents of minor children. The Alternative is designed to strengthen family bonds and improve parenting skills to encourage successful reintegration. An overview of the Alternative's history, design, and implementation is presented, followed by preliminary results from an impact evaluation. A case study of a successful participant is presented, and implications for the findings are discussed.